Peranan Pendapatan Asli Daerah (PAD) Dan Dana Perimbangan Terhadap Pendapatan Domestik Regional Bruto (PDRB) Serta Dampaknya Terhadap Pertumbuhan Ekonomi Daerah - Nuryasman MN (Jurnal Ekonomi, 2012)
Looking at the phenomenon that appears in the implementation of regional autonomy, the study sought to examine several issues, mainly related to the Gross Regional Domestic Product (PDRB) and regional economic growth (Growth), such as The role and influence of local revenue (PAD) and Fund Balance (DAU, DAK, and DBHPBP) to the Gross Regional Domestic Product (PDRB). The role and influence of the PAD, DAU, PDRB, and DBHPBP on regional economic growth. This study attempted to analyze these two problems, using a panel data approach using Fixed Effect Model (FEM) and the Random Effect Model (REM), as well as data processing method using the Two-State Least Square (TSLS), the analysis period from 2005 to 2010 and object of research as much as 33 provinces. From the analysis, the obtained results are as follows: After conducting tests Hausmann (Hausrnann Test) on both models (FEM and REM) model is the best to use Fixed Effect Model (FEM) with General Least Square by White Heteroscedasticity, both for the problems first and the second one. For the first problem, obtain the relationship and influence positive and significant association between PAD, DAU and DBHPBP of PDRB, whereas DAK has a relationship and influence positive but not statistically significant of PDRB. Taken together all the independent variables (PAD, DAK, DAU and DBHPBP) contribute to changes in PDRB amounting to 97.50% and the rest of 2.50% is influenced by other variables outside the model. For the second problem, PDRB, PAD, DAU and DBHPBP all statistically significantly affect economic growth, but only variable PAD which has a relationship and a negative effect on PDRB, while the other variables have a positive relationship and influence. Donations of all these variables together on economic growth is high at 99.30% and the influence of other variables outside the model of only 0.70%.